PENGARUH UKURAN BUTIR KARET BAN BEKAS TERHADAP KARAKTERISTIK MARSHALL PADA CAMPURAN ASPHALT CONCRETE-BINDER COURSE - Heriadi; Agus Taufik Mulyono; Latif Budi Suparma (Jurnal HPJI (Himpunan Pengembangan Jalan Indonesia), 2023)
Abstract Crumb Rubber, obtained through retreading of used rubber tires, has the opportunity to be used in asphalt mixtures, thereby reducing the waste of used tire rubber. The purpose of this study was to analyze and compare the effect of adding Crumb Rubber with large particle sizes, which is passing sieve Number 4 and being retained by sieve Number 8, and small particle sizes, which is passing sieve Number 16, in the Asphalt Concrete-Binder Course mixture. The effect of Crumb Rubber is measured using the Marshall and Indirect Tensile Strength parameters. The proportion of addition of Crumb Rubber is 0% and 1.5% of the total weight of the aggregate. The binder used in this study was Penetration Grade Asphalt of 60/70, produced by Shell. This study shows that the addition of Crumb Rubber increases the values ​​of Void in Mineral Aggregate, Void in Mix, and Marshall Flow, but decreases the values ​​of density, Void Filled with Asphalt, Marshall Stability, Marshall Quotient, and Retained Marshall Stability, as well as decreases the values of Indirect Tensile Strength. Crumb Rubber with small particle size turned out to have a better effect than Crumb Rubber with large particle size. Keywords: Crumb Rubber; asphalt mixture; Marshall Parameters; Indirect Tensile Strength Abstrak Crumb Rubber, yang didapat melalui vulkanisir ban karet bekas, mempunyai peluang untuk dipakai dalam campuran beraspal, sehingga dapat mengurangi limbah karet ban bekas. Tujuan penelitian ini adalah untuk menganalisis dan membandingkan pengaruh penambahan Crumb Rubber dengan ukuran butir besar, yaitu lolos ayakan Nomor 4 dan tertahan ayakan Nomor 8, dan ukuran butir kecil, yaitu lolos ayakan Nomor 16, pada campuran Asphalt Concrete-Binder Course. Pengaruh Crumb Rubber diukur dengan menggunakan parameter Marshall dan Indirect Tensile Strength. Proporsi penambahan Crumb Rubber adalah 0% dan 1,5% terhadap berat total agregat. Bahan pengikat yang digunakan pada studi ini adalah Aspal Penetrasi 60/70 produksi Shell. Penelitian ini menunjukkan bahwa penambahan Crumb Rubber meningkatkan nilai-nilai Void in Mineral Aggregate, Void in Mix, dan Marshall Flow, tetapi menurunkan nilai-nilai kepadatan, Void Filled with Asphalt, Marshall Stability, Marshall Quotient, dan Rentained Marshall Stability, serta menurunkan nilai Indirect Tensile Strength. Crumb Rubber dengan butir kecil ternyata memberi pengaruh yang lebih baik daripada Crumb Rubber butir besar. Kata-kata kunci: Crumb Rubber; campuran beraspal; Parameter Marshall; Indirect Tensile Strength